Rancang Bangun Sistem Informasi Manajemen Kepegawaian dengan Metode the Open Group Architecture Framework (Toga F) - Meuthia Rachmaniah; Hari Agung Adrianto; Abdul Aziz (Jurnal Ilmu Pertanian Indonesia, 2013)
The personnel administration process for functional staff follow bureaucratic procedures that is time consuming and often difficult to monitor. Further, the process will be prolonged if the process is handled manually. These conditions are often limit staff managers at unit level, technical implementation unit (UPT), or functional staff who need the information timely in a precise and accurate format. Manual handling cannot support the information speed, because staffs have to manually track file(s) or documents in the chain of bureaucracy that is complex and tedious. Delays in the process of obtaining such information could lead toadverse consequences in financial terms if for instance the termination in functional status and monthly salary occurred. One solution to this problem is to develop an online personnel information system (SIMPEG) to accelerate personnel information services. The Design of the online SIMPEG development utilized the method of open group architecture framework (TOGAF) while the system development implemented prototype method. Further the prototype is tested using developed questionnaires. In general the results of this study contribute to personnel information service acceleration. The promotions process (KP) was accelerated to 66.67% i.e. from 11-12 months to 4-3 months. Personnel time off and personnel reinstated (ABK) also accelerated by 66.67% that is previously taken 5-6 months to 2 months. While the process of scholarship approval was accelerated by 50% compared to the old system which was 3-4 months to 2 months.